Pengaruh Ekstrak Daun Kemangi (Ocimum sanctum L.) Terhadap Kelarutan Kalsium Batu Ginjal - Sumarni, Wiwin; Sabang, Sri Mulyani; Ratman, Ratman (Jurnal Akademika Kimia, 2017)
The aim of the study is to determine dissolving power and the solubility of calcium on kidney stone by the extracts of basil (Ocimum sanctum L.) and determined the effect of basil leaves extracts concentration (%)on the solubility of kidney stones calcium. The method used the extraction infuse way. Variation of concentration extracts were 5%, 10%, 15%, 20% and 25%. The solubility of calcium in basil leaves extracts was determined by SpectroDirect. The results showed that concentration of 5% dissolved by 15.38% of calcium; concentration of 10% dissolved by 21.05%; concentration of 15% dissolved by 26.92%; concentration of 20% dissolved by 35.71%, and concentration of 25% dissolved by 42.10%calcium. It can be concluded that the extracts of basil leaves dissolved kidney stones calcium. The solubility tests showed that the higher the concentration of the basil leaves extracts than the greater the solubility.